Hubungan antara Kepercayaan Diri dengan Kecemasan Bertanding Anggota Komunitas Tari Modern di Kota Padang - Ajeng Wulandari; Harry Theozard Fikri; Krisnova Natasia (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The aim of this study is to assess the relationship between self-confidence and competing anxiety A member of the Padang City Modern Dance Community. In this study the independent variables are self-confidence, and the dependent variable is anxiety for competition. The measuring instrument used in this study is a level of selfconfidence and a competing scale of anxiety.In this study the sampling technique uses the technique of nonprobability sampling. 105 members of the modern dance community in Padang city were the sample in this study. Alpha Cronbach technique was used in validity and reliability tests in this study. The validity of coefficient results on the confidence scale moves from rx-0.341 to r-0.889 with a reliability coefficient of a-0.943, while the competition anxiety scale moves from rix0.324 to r-0.737 with a reliability coefficient of a = 0.919. The correlation value was -0.571, with a meaning level of 0.000, which means the hypothesis is accepted, based on the data analysis.This indicates a relationship significant among the members of the modern dance community in Kota Padang between self-confidence and competing anxiety.